East Meets West in the Fiction of Kamala Markandaya: Exploring the East-West Encounter in Kamala Markandaya's Post-Independence Novels (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Themes of most of Indian novels of post-independence era revolves around struggle India was going through. In Indian English literature, Kamala Markandaya is one women author who has created pedestal place in English literature. East west encounter has emerged as prominent theme in the fiction of Kamala Markandaya apart from feminism. Here in this research paper, i will discuss, different ways east meets west in her novel. She has used characters, cultures, way of life to differentiate between east and west. We can see in her novels, indo-British interaction in india and outside india, cultural conflict, rural versus urban, mysticism versus science, faith versus reason. How plot shifts when east meets west. How people behave differently to culturally different people. Her characters struggle at individual level, social level, cultural level, political level and racial level. All her novels are of post-independence era, novelist truly present what a developing country goes through. Novelist has herself lived both the life, in India and abroad, so she justly presented this. In some case, she presented western characters as savior while in some case they are brutal racist. I will discuss in my paper how conveniently she showcased east west theme in her fiction.